Problems caused by early blight at potato crops - Kapsa, Józefa; Osowski, Jerzy (MTT, 2007)
Early blight, economically damaging foliar disease of potato, is caused by two species of Alternaria genus: A. alternata (Fries.) Keissler and A. solani Sorauer.The disease occurs commonly worldwide on potato crops, particularly in regions with alternating periods of dry weather and high humidity, which favour spore formation and disease development. Harmfulness of early blight is estimated differently in various regions of the world. According to Reinoch (1974), the disease reduces yields up to 25%, locally 60%. According to Johnson et al. 1986, Fry 1994, maximum documented yield reductions are usually 20- 30%. In Polish climatic conditions high regional losses caused by early blight were recorded, however, most were related to cultivars with recognized susceptibility to this disease or weakened by infection of viruses. In the recent years tuber losses in Poland balanced from 6 to 45% (Kapsa & Osowski 2004). In the years 1998-2006, in cooperation with the Plant Health and Seed Inspection Service an evaluation of early blight occurrence on potato crops was carried out throughout Poland. Observations revealed that the disease occurrence on potato crop is common in most production areas, average at 86% of observed crops. Early blight occurs usually at the end of May or the beginning of June, earlier than late blight which is observed mainly in June. In Polish climatic conditions our recommendations regarding the first chemical treatment for protection of susceptible cultivars indicate that, the appearance of the first disease symptoms on potato leaves, is the optimum time for initiating applications of fungicides. In some countries potato crops are regularly irrigated (USA and the Netherlands) and then the early blight occurs at the end of growing season on aging plants. The recommendations for potato protection against the early blight, aiming at tuber protection from pathogen infection, refer to the end of the season as the best time for fungicide application (Fry 1994).
Keywords: Ka; potato; fungal disease; early blight